Contracts for difference - CfDs - in the energy transition: Balancing market efficiency and risk mitigation - Abolfazl Khodadadi; Rahmatallah Poudineh (The Oxford Institute for Energy Studies, 2024)
Contracts for Difference (CfDs) have emerged as a key policy instrument to incentivize renewable energy investments by mitigating revenue volatility. However, conventional CfDs, while effective in fostering growth in renewable energy sources, can introduce market distortions. These distortions arise from misaligned incentives, particularly the 'produce-and-forget' mentality, where generators prioritize maximizing production without considering market signals. To address these challenges, in recent years, alternative CfD designs have been proposed in the literature with the aim of enhancing market integration by decoupling payouts from real-time generation, and aligning generator incentives with market outcomes. However, the challenge is that these modified CfDs introduce basis risk, where discrepancies between reference prices and output, and actual prices and output, can lead to financial volatility. This is however unavoidable because the purpose of CfDs is to mitigate risks for renewable energy generators, while market efficiency relies on participants bearing some level of risk through price exposure, so as to incentivize optimal decision-making. This challenge underscores the complex trade-off policymakers face between market efficiency and risk mitigation, necessitating a balanced approach to the design of CfDs. Additionally, the impact of increased basis risk on various stakeholders, including generators, the government, consumers and financial institutions, highlights the need for a nuanced understanding of financial volatility and regulatory implications of alternative CfD designs.
Keywords: 330; CFD; generation independent CfD; market efficiency; Renewable energy support scheme; risk mitigation; yardstick CfD